Optimal microchannel planar reactor as a switchable infrared absorber - Alston, Mark E. (Cambridge University Press, 2017)
This paper will propose methods to use leaf vasculature formations to advance a material to act as an infrared block. The research shows the use of microfluidics based flows to direct the structural assembly of a polymer into a thermally functional material. To manage IR radiation stop-band to lower a polymer device phase transition temperature. This paper will determine this functionality by hierarchical multi microchannel network scaling, to regulate laminar flow rate by analysis as a resistor circuit.